If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -1b = 7v Solving 8 + -1b = 7v Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1b = -8 + 7v Combine like terms: 8 + -8 = 0 0 + -1b = -8 + 7v -1b = -8 + 7v Divide each side by '-1'. b = 8 + -7v Simplifying b = 8 + -7v
| (-5+5n)(-6)-(7-4d)(-2)= | | -3(-4y+u)-5(-6u-6y)= | | 1.8b=0.9 | | 8(2)=3(x+3) | | 8(x-3)=6x+11-5x | | 42+22x=180 | | 13x+9x-8+50=180 | | 5x+90=2x-15 | | (32x-7y)-(28x-11y)=0 | | 1.6h+72=4h-30 | | -30x^2+35x-10=0 | | -4.42x+.9=-9.070-0.432 | | 11x-10y=30 | | 60+.50(200)=1.30(200) | | 20x-9(3)=7 | | 19+[3x(7-3)]-2= | | .5(-4x-5)=7x-.5 | | 3x^3-3x^6-9x^3+5=0 | | 65-85=x | | (x-1)(2x)(x-4)=40 | | 5d-33=7.2 | | 32x=5x-14 | | r/3-4=3 | | 3x-(2x-1)=5x+1-4x | | 60+.50(100)=1.30(100) | | -5.26+.21x=19.94 | | 7cos(7x)=0 | | 16x^2-4x+5-(16x^2-8x)+1=0 | | -12x-11=-47 | | 7(-8x)= | | -4x=12-x^2 | | -z-9=3.4(2z+4.3) |